Aplikasi Pengelola Keuangan Pribadi Berbasis Android - Andi Susanto; Agustinus Noertjahyana; Alexander Setiawan (Jurnal Infra, 2016)
Personal financial management is important in supporting the realization of someone's goals. By doing personal financial management, each individual knows the goals to be achieved, so each individual have to optimally utilize the management of financial resources to achieve goals. Many young people today has not been able to plan and control the use of money to achieve goals. Other than that, young people is also lazy to record the costs of his daily expenses because they have to recorded manually on paper. With a gadget that can be taken anywhere and easy Internet access, then designed application that can help record the expense costs or income daily. In this research, Android-based personal finance manager application will be made in this thesis. This application has a feature that can help user to control the use of their money in graphical form, reminder for paying debt and paying credit card bills, limiting budget, create their own savings, and see the real time  exchange rate.Based on the result of the implementation and testing, the application can  provide both income and expense reports in graphical form, also can remind user to pay debt according to the date that user set, and remind user to pay credit card bills before the due. With this application, users can manage their personal finances to achieve their goals.